1991
DOI: 10.1212/wnl.41.10.1633
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral occipital lesion causing hemianopia affects the acoustic saccadic programming

Abstract: Infrared oculographic recordings of saccades evoked by auditory or visual targets in four patients with hemianopia due to an occipital lesion showed that these patients employed a different strategy to find visual and auditory targets in each hemifield. In the seeing hemifield, the patients acquired auditory targets with both monosaccadic and multiple saccadic refixations. The first saccade, the largest, brought the eyes toward the target; the following smaller saccades completed the search as in normal subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nevertheless, our group of neuro-ophthalmic patients had higher temporal lags and spatio-temporal latencies than controls (see Figures 2A,B). Numerous studies have shown that patients with neuro-ophthalmic VFD have prolonged latencies compared to controls in response to moving or stationary targets -often in the range of 20-100 ms more than controls (Sharpe et al, 1979;Meienberg et al, 1981;Traccis et al, 1991;Rizzo and Robin, 1996;Barton and Sharpe, 1998;Fayel et al, 2014). Our group has previously shown through simulations (Grillini et al, 2018;Gestefeld et al, 2020) and in actual patients (Soans et al, 2021) that this is indeed the case.…”
Section: Assigned Clustermentioning
confidence: 55%
“…Nevertheless, our group of neuro-ophthalmic patients had higher temporal lags and spatio-temporal latencies than controls (see Figures 2A,B). Numerous studies have shown that patients with neuro-ophthalmic VFD have prolonged latencies compared to controls in response to moving or stationary targets -often in the range of 20-100 ms more than controls (Sharpe et al, 1979;Meienberg et al, 1981;Traccis et al, 1991;Rizzo and Robin, 1996;Barton and Sharpe, 1998;Fayel et al, 2014). Our group has previously shown through simulations (Grillini et al, 2018;Gestefeld et al, 2020) and in actual patients (Soans et al, 2021) that this is indeed the case.…”
Section: Assigned Clustermentioning
confidence: 55%
“…Saccade endpoint accuracy is not considered due to the large stimulus eccentricities. Hemispherectomized patients are also known generally to use different movement strategies to acquire targets in the seeing and blind hemifields (Herter & Guitton, 2007;Traccis, Pulgia, Ruiu, Marras, & Rosati, 1991). Saccade metrics are not considered because the EOG signal is inherently too noisy to permit accurate velocity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, current knowledge about the impairment of saccadic eye movements in patients with cortical damage including early visual cortices is sparse and rare (Barton, 2001;Leigh and Kennard, 2004). One of the exceptions is a study that examined saccades to auditory targets in patients suffering from hemianopia attributable to occipital lesions (Traccis et al, 1991). This result implies that occipital lesions influence a common mechanism of saccade control used for visual and auditory targets.…”
Section: Discussionmentioning
confidence: 99%